Pemasaran Digital Usaha Keripik Singkong sebagai Optimalisasi Pemberdayaan UMKM Desa Kebonadem - M. Fatur Rizki; Arina Hidayati Hasanah; Muhammad Arfaq Aqil; I’tibar Ikhsan; Alivia Maghfiroh; Dwi Hartanti (Lembaga Pengembangan Kinerja Dosen, 2024)
The main objective of this kkn activity is to increase the visibility, competitiveness, and revenue of MSMEs through product promotion on social media platforms. The main problem faced by MSMEs is limited knowledge in developing innovative products, which hinders the ability to compete with foreign products. Therefore, the urgency of this project lies in the importance of supporting MSMEs in utilizing digital media to improve their competitiveness. The results of this video creation show significant positive impacts, including increased product visibility, increased sales, and improvements in the packaging process. Not only did the video capture the attention of consumers, but it also helped build closer relationships between producers and consumers through social media. These results confirm the importance of visual content in digital marketing strategies for MSMEs, as well as the need to innovate and develop the brand on an ongoing basis.